Perlindungan Hukum pada Korban Pelecehan Seksual Terhadap Tuduhan Pencemaran Nama Baik - Mars Akbar Aziz Prakoso; Mirza Elmy Safira; Budi Handayani (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Article 28 I of the Constitution of the Republic of Indonesia mandates that every citizen has the right and everyone has the right to be free from discriminatory treatment and entitled to protection thereof. Many people believe that only women can be victims of harassment. Women and men are both potential victims and the effects they get are the same. MS as a victim of sexual harassment in KPI wrote an open letter on social media about the sexual harassment that happened to her. The open letter then went viral and many social media users began to harass the personal lives of these perpetrators. From here, the perpetrators reported back to MS with allegations of defamation. The incident became the author's background in writing this research by applying normative juridical research methods, namely research that focuses on positive law or the practice of applying norms or rules in legislation. According to Article 310 paragraph (3) of the Criminal Code states that it cannot be punished if the accusation is carried out as a form of defending public interests or defending oneself. While what is known today, MS who tells her condition after being harassed on social media is an attempt to defend herself and reveal the truth.